Intention to Use Smartphones among Peruvian University Students - Rojas-Osorio, Mercedes; Alvarez-Risco, Aldo (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This document is a report on the findings of a study aims to investigate human motivations affecting an adoption decision for smartphone among Peruvian university students. This research investigates smartphone users’ perception using a technology acceptance model (TAM). It is analyzed perceived ease of use, perceived usefulness and attitude toward to keep using a smartphone as determinants for behavioral intention to keep using a smartphone between Peruvian university students, evaluating them with reliability and validity and confirming the hypotheses elaborated for the study. Findings indicate that the behavioral intention to keep using a smartphone (BIU) was significantly influenced by perceived ease of use (PEOU), perceived usefulness (PU) and attitude toward to keep using a smartphone (AKUS) and also, PEOU influenced significantly to PU. This study not only provides valuable information about students´ the intention to keep using a smartphone but also enriches the current literature, focusing on Peru, which has a different commercial characteristic and cultural background as compared to North America, Europe, and Asia. According to the current literature review, this is the first study on this subject that specifically focuses on the use of smartphones by Peruvian university students.